2022
DOI: 10.5851/kosfa.2022.e38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying Methods on Physicochemical Characteristics and Functional Properties of Duck Blood Gel

Abstract: The drying of duck blood provides safety and commercial benefits, but each drying method has its own characteristics. Moreover, information on the effects of diverse drying methods on the quality of duck blood is limited. This study aimed to investigate the effects of various drying methods on the chemical and functional properties of duck blood. The physicochemical characteristics and functional properties of duck blood subjected to spray drying (SD), freeze drying (FD), vacuum drying (VD), and hot air drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…study. A previous study speculated that plasma protein denaturation may have occurred during the freeze-drying of blood (Kim et al, 2022). From these results, we conclude that the addition of KG before freeze-drying did not negatively contribute to the thermal stability of duck blood gel.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 49%
See 4 more Smart Citations
“…study. A previous study speculated that plasma protein denaturation may have occurred during the freeze-drying of blood (Kim et al, 2022). From these results, we conclude that the addition of KG before freeze-drying did not negatively contribute to the thermal stability of duck blood gel.…”
Section: Differential Scanning Calorimetrysupporting
confidence: 49%
“…The pH of the heat‐induced gel with FDB + KG was higher than that of the control (FDB alone) gel ( p < 0.05). Metal ions (iron ions) present in the blood can cause oxidation when they come into contact with oxygen ions, and this can lead to a decrease in pH (Kim et al., 2022; Sorapukdee & Narunatsopanon, 2017). It had been reported that the adsorption of metal ions on KG may prevent this pH decrease (Niu et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations